1998
DOI: 10.1074/jbc.273.46.30688
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae TSC10/YBR265w Gene Encoding 3-Ketosphinganine Reductase Is Identified in a Screen for Temperature-sensitive Suppressors of the Ca2+-sensitive csg2Δ Mutant

Abstract: Saccharomyces cerevisiae csg2⌬ mutants accumulate the sphingolipid inositolphosphorylceramide, which renders the cells Ca 2؉ -sensitive. Temperature-sensitive mutations that suppress the Ca 2؉ sensitivity of csg2⌬ mutants were isolated and characterized to identify genes that encode sphingolipid synthesis enzymes. These temperature-sensitive csg2⌬ suppressors (tsc) fall into 15 complementation groups. The TSC10/YBR265w gene was found to encode 3-ketosphinganine reductase, the enzyme that catalyzes the second s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
185
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(194 citation statements)
references
References 24 publications
8
185
1
Order By: Relevance
“…These results suggested that the loss of MIPC synthesis and the change in the hydroxylation levels in sphingolipids can broadly affect the phenotypes caused by the deletion of V-ATPase. As reported previously, sur1D csh1D cells exhibited supersensitivity to Ca 2+ , and the sensitivity was rescued by the deletion of SUR2 or SCS7 (Beeler et al, 1998;Zhao et al, 1994) (Fig. 7a, b).…”
Section: Effects Of Increases and Decreases In The Hydroxylation Levesupporting
confidence: 62%
See 2 more Smart Citations
“…These results suggested that the loss of MIPC synthesis and the change in the hydroxylation levels in sphingolipids can broadly affect the phenotypes caused by the deletion of V-ATPase. As reported previously, sur1D csh1D cells exhibited supersensitivity to Ca 2+ , and the sensitivity was rescued by the deletion of SUR2 or SCS7 (Beeler et al, 1998;Zhao et al, 1994) (Fig. 7a, b).…”
Section: Effects Of Increases and Decreases In The Hydroxylation Levesupporting
confidence: 62%
“…S1). The Ca 2+ supersensitivity of MIPC synthesis-deficient mutants is caused by the accumulation of IPC-C (Beeler et al, 1998;Zhao et al, 1994), and the cell death under nitrogen starvation due to the loss of MIPC synthesis is rescued by the deletion of SUR2 or myriocin, both of which prevent the accumulation of IPC-C (Yamagata et al, 2013). However, the growth defect of sur1D csh1D vma2D cells at pH 7.2 was not suppressed on the deletion of SUR2 or SCS7 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other suppressors of Ca 2ϩ sensitivity in the csg2 mutant were found to be genes involved in signal transduction. These included genes encoding the protein kinase TOR2 and the phosphatidylinositol-4-phosphate 5-kinase MSS4 (9). Tor2p functions in a nutrient-sensing signaling cascade and in cell cycle-dependent reorganization of actin cytoskeleton (26 -30).…”
Section: Discussionmentioning
confidence: 99%
“…The Ca 2ϩ -sensitive phenotype of the csg2 mutant was suppressed by several mutations that caused a reduction in the IPC-C concentrations (6). These mutations included genes involved in long chain base synthesis (lcb1, lcb2, tsc3, and tsc10) (6,9,15), palmitoyl-CoA synthesis (fas2) (9), elongation of very long chain fatty acids (tsc13) (9,16), conversion of DHS to phytosphingosine (sur2) (1), and hydroxylation of very long chain fatty acids (scs7) (1). Moreover, overproduction of Ccc2p, which may stimulate the conversion of IPC-C to IPC-D, also rescued the Ca 2ϩ -sensitive phenotype of the csg2 mutant (3).…”
Section: Discussionmentioning
confidence: 99%